Asymmetric septal thickening is observed in hypertrophic cardiomyopathy mutation carriers without left ventricular hypertrophy: insights from AI analysis. (23rd August 2022) - Shiwani, H; Hughes, R K; Camaioni, C; Augusto, J B; Knott, K; Rosmini, S; Burke, L; Pierce, I; Moon, J C; Davies, R H
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Dr Hughes is supported by the British Heart Foundation (grant number FS/17/82/33222). Background: Hypertrophic cardiomyopathy (HCM) is a common inherited cardiac disease characterised by left ventricular hypertrophy (LVH), often, with asymmetric septal thickening. Despite the prevalence of inherited mutations present in >50% of cases, there is variable phenotypic expression in those with abnormal sarcomere protein genes. In individuals with abnormal genes but without LVH, we hypothesised that there is subtle asymmetric septal hypertrophy, detectable by the increased precision offered by an artificial intelligence (AI) tool for measuring wall thickness. Purpose: We explored the septal-lateral ratio measured by AI in individuals with an identified genotype but no left ventricular hypertrophy as a component of sub-clinical HCM. Methods: 43 individuals with identified genotype, but no left ventricular hypertrophy (G+LVH-) and 97 age-, sex- and disease-matched controls underwent CMR. Patients were excluded if they had a maximum wall thickness (MWT) of ≥13mm. A clinically validated AI tool was used to measure the MWT, for each segment in the 16-segment AHA model. The septal-lateral ratio was calculated using the septal segment with the largest MWT and the lateral segment with the largest MWT. Results: The mean septal-lateral ratio of the G+LVH- patients was 1.22 (SD 0.22) and the mean septal-lateral ratio of the matched controls was 1.14 (SD 0.15) with a statistically significant mean difference of 0.08 (p=0.01). There was no significant difference between the MWT of the G+LVH- patients at 10.3mm (SD 2.2) and healthy volunteers at 10.1mm (SD 1.8) (p = 0.61). Conclusion: G+LVH- patients have a 7% increase in their septal-lateral ratio compared with age-matched controls despite the lack of difference in the MWT. Using increased precision offered by AI, early features of HCM can be observed in patients without overt LVH.